The Perfect Imperfections of Perovskite Oxide Catalysts in the Aspect of Defect Equilibria - Maria Christy; Seunggun Choi; Jiseok Kwon; Jinwoo Jeong; Ungyu Paik; Taeseup Song (Small Science)
ABX3 (X = O) perovskite oxides are an uprising class of alternative electrocatalysts in eminent technologies like electrocatalysis, photocatalysis, thermocatalysis, and energy storage. The perquisites of perovskite oxide catalysts encompass ordered atomic structure, structural/compositional extensibility, flexible electronic structure, lucrativeness, and so on. The ingenuity to precisely control and tune the inherent properties by reconstructing their crystal structure is particularly advantageous in electrocatalysis reactions like oxygen reduction and evolution reactions (ORR and OER). Incorporating multidimensional imperfections in the presumably perfect crystal structure of the perovskite catalysts is garnering booming attention among researchers. This concept can expertly influence the electronic structure and boost the reaction kinetics during electrocatalysis. Defects or imperfections are achieved by substituting A‐ and/or B‐sites with heteroatoms or by oxygen vacancies. Defect engineering points to a promising new direction in the development of perovskite oxide catalysts. This work surveys the recent progress in defect engineering and how it plays a vital role in their design, and application in electrocatalysis, mainly ORR/OER. The architecture, dimensionality, and the types of perovskite oxides based on their cations, crystal structures, and stoichiometries are surveyed for a comprehensive understanding. This review aims to provide an extensive outlook on oxide perovskite catalysts concerning structural defects.